Underdiagnosed Complicated Plasmodium vivax Malaria in a Child: Need to Think - Sonu AGRAWAL (Iranian Journal of Parasitology, 2017)
Malaria is major cause of morbidity and mortality worldwide. The highest incidence of malaria in the world is South East Asia. India is most affected country followed by Indonesia and Myanmar. The prevalence of malaria varies according to geographical region. Diagnosis of malaria infection has been underestimated. Here, we report a case of under-diagnosed complicated vivax malaria in one-yr-old child in 2016. Early diagnosis and prompt treatment can reduce both morbidity and mortality in complicated malaria infection.